2017
DOI: 10.1016/j.neuron.2016.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic, Cell-Type-Specific Roles for GABAergic Interneurons in a Mouse Model of Optogenetically Inducible Seizures

Abstract: SUMMARY GABAergic interneurons play critical roles in seizures, but it remains unknown whether these vary across interneuron subtypes or evolve during a seizure. This uncertainty stems from the unpredictable timing of seizures in most models, which limits neuronal imaging or manipulations around the seizure onset. Here, we describe a mouse model for optogenetic seizure induction. Combining this with calcium imaging, we find that seizure onset rapidly recruits parvalbumin (PV), somatostatin (SOM), and vasoactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
156
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(172 citation statements)
references
References 31 publications
14
156
0
Order By: Relevance
“…There is evidence, including the data presented here, that the local interaction of excitatory and inhibitory circuits is crucial for successful or failed ictal progression (Cammarota et al, 2013; Hunt et al, 2013; Khoshkhoo et al, 2017; Sessolo et al, 2015; Trevelyan et al, 2006; Ziburkus et al, 2006). While several recent studies have shown promising results with respect to cell sub-population based therapeutic seizure intervention (Krook-Magnuson et al, 2013; Ledri et al, 2014), others have raised concerns about the potential seizure promoting effects of such therapies (Avoli and de Curtis, 2011; Fujiwara-Tsukamoto et al, 2010; Gnatkovsky et al, 2008; Grasse et al, 2013; Sessolo et al, 2015).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…There is evidence, including the data presented here, that the local interaction of excitatory and inhibitory circuits is crucial for successful or failed ictal progression (Cammarota et al, 2013; Hunt et al, 2013; Khoshkhoo et al, 2017; Sessolo et al, 2015; Trevelyan et al, 2006; Ziburkus et al, 2006). While several recent studies have shown promising results with respect to cell sub-population based therapeutic seizure intervention (Krook-Magnuson et al, 2013; Ledri et al, 2014), others have raised concerns about the potential seizure promoting effects of such therapies (Avoli and de Curtis, 2011; Fujiwara-Tsukamoto et al, 2010; Gnatkovsky et al, 2008; Grasse et al, 2013; Sessolo et al, 2015).…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, and consistently in awake mice, interictal periods and seizure durations displayed a rather irregular pattern. At times, ictal activity failed to invade or only incompletely penetrated the imaged territory (Figure 5B left, Figure 5C left), and there was a consistent delay between the electrographic seizure onset and optical break-in, on the scale of seconds (Figure 5B and C, magnified portions) (Khoshkhoo et al, 2017; Martinet et al, 2015). This observation could be explained by a much slower temporal seizure progression imaged during wakefulness as compared to the anesthetized condition (4-AP: 0.0215 ± 0.003 mm/sec [5exp., awake] versus 0.64 ± 0.18 mm/sec [7exp., anesthetized]).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Calcium imaging of optogenetically kindled neocortical seizures demonstrates that inhibitory parvalbumin and somatostatin interneurons are activated prior to the excitatory neurons in the SOZ. 43 The mechanism by which the specific excitatory/inhibitory imbalance at LVF onset promotes seizure genesis is not yet resolved but may involve depolarizing GABAergic activity 45 or potassium and chloride efflux due to activation of the KCC2 cotransporter. 46,47 It is possible that novel pharmacological interventions could reduce inhibitory interneuron overactivation and thereby prevent seizure evolution.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] These effects have been obtained by inhibiting excitatory principal cells 6 or by increasing the excitability of inhibitory interneurons. 9 However, it has been reported that optogenetic stimulation of interneurons can also trigger ictal discharges in vitro, in the 4-aminopyridine (4AP) model. 9 However, it has been reported that optogenetic stimulation of interneurons can also trigger ictal discharges in vitro, in the 4-aminopyridine (4AP) model.…”
mentioning
confidence: 99%